Participation of men attending outpatient services at Qoaling Filter Clinic in family planning - Ralejoana, Ntsoaki (University of Limpopo (Medunsa Campus), 2010)
Introduction The neglect of men with respect to their role in family planning has contributed to a situation in which men remained passive or non-participatory in reproductive health related studies and have generally not been included in most of research on family planning and use of modern contraceptives (Mbizvo & Basset, 1996). Family planning saves women’s and children’s lives and improves the quality of life. In addition, family planning reduces fertility and help to relieve the pressures that rapidly growing populations place on economic, social and natural resources. Men’s participation in family planning can improve women and children’s health. Men are heads of families and play dominant roles in decision making crucial to women’s lives and women’s reproductive health. Aim and the objectives of the study: The aim of the study was to identify and describe factors affecting the participation of men attending out - patient services at Qoaling Filter Clinic. Methods and materials: • Study design The study used a descriptive cross sectional design. The factors were identified, described and the differences between the factors and participation determined. • Study population The population for the study consisted of men between 18 and 50 years who attended out-patient services at Qoaling Filter Clinic. • Study setting The data was collected from Qoaling Filter Clinic which is situated the southern region of Maseru, the capital of Lesotho. It is a mini hospital. • Sampling and sample size A cluster sampling was used. The researcher developed a sampling frame. Men who met the inclusion criteria were selected randomly. The formula used to compute the sample size was n/ [(1-(n/population)]. The sample size was 94. Results The findings of this study indicated that men knew some of the family planning methods. There was no difference in participation of men in family planning between men with more or less knowledge. There was a relationship between age, residing area, knowledge and participation. The majority of men indicated that if they were given information and there were special clinics for men, family planning services utilization would increase and they can be more involved in family planning services and support their wives and partners. Conclusion Men’s knowledge on family planning can improve their participation in utilizing the services and supporting their partners. Through participation men can help slow the spread of HIV and AIDS and sexually transmitted infections, unwanted pregnancies and criminal abortions
Thesis (MPH)--University of Limpopo, 2010.
Keywords: Outpatient services; Family planning